The Philosophy of Technology and Engineering - Durmuş Günay (Üniversite Araştırmaları Dergisi)
In this study, first, we will address the meaning of engineering, engineer and technology. The purpose here is to clarify these concepts and show the relationships between them. Technology has always been a difficult concept to understand and express exactly what it is. To understand easily what technology is, in this study, we take advantage of the philosophy of Aristotle, we will try to put forward a new explanation style. In other words, we will try to present a technology philosophy based on Aristotle’s philosophy and also its relation with the engineering science. Secondly, we will look at the history of engineering in the contexts of the technological development. Lastly, we will also address the new trends and approaches in the engineering education in the world at the beginning of the 21st century and today. Since engineering education is also being transformed in accordance with the possibilities brought about by technology in the education field and the needs and demands of society.